Design and Implementation of a Digital Controller System for a Turbo-Generator - Shakkour, Fadi (Department of Electrical Engineering, 2024)
Laboratory turbo generators are systems that help to give a better understanding of the concept of a real power plant based on a turbo generation. They are built to have flexibility in some parameters, such as different fuels, different temperatures, fuel consumption, etc. This flexibility leads to each turbine being entirely unique. Thus, it becomes difficult to apply the regular models which are taught in literature, to control the outputs or predict the behavior of the turbines. This dissertation studies the behavior of the laboratory turbo generator located in ORT Braude College, according to inputs of fuel consumption and excitation voltage on the rotor, compared to the outputs of frequency and voltage on the load. This specific turbo generator is a twin-shaft generator, which means that it is used for wide range of output frequency, which is the opposite of traditional power plant requirements. From initial measurements, it was deduced that the system is an inherently unstable open-loop system for a wide range of frequencies which are available for the generator, between 1000 RPM and 8000 RPM. By using the Bristol gain numbers, it was shown that no controller may be designed to regulate both outputs independently by the given inputs for the system, as it requires a larger scope of the input than the system is physically able to give. The author proceeded by deeper analysis of the system, to model the turbo generator and have a better understanding of the connection between the inputs and outputs, to do so the connection between Bristol gains and quantitative feedback theory is achieved. The analysis started by laws of energy conservation, then to include experimental data to understand the connection between energy, efficiency, magnetic flux, fuel flow and excitation voltage and how they are connected to the rotation of the rotor in the generator. It was shown using Bristol gains that, unlike in power plants, the efficiency is strongly connected to the speed of the generator shaft, and proved again how, for this system, it is physically impossible to design a 2 × 2 controller and gave a better understanding for choice of input-output pairing due to weak coupling. As a conclusion from this analysis, a single SISO (single input single output) digital controller was designed, where the load frequency is controlled by the excitation voltage, which is the opposite of how a conventional power plant is controlled. The author uses a proportional and international controller by using “Ed's PI controller” (Professor Eduard Eitelberg) to overcome possible issues in the integration part. The controller was designed using the analysis of the turbine by implementing it in MATLAB, to have an initial theoretical digital proportional-integral controller and test it in a simulation using SimulinkMATLAB. The final step was to implement the controller through a micro-controller (teensy3.6) to do the calculations using software. The usage of a micro-controller requires an interface between it and the turbo generator as they work on different range of voltages. To overcome the difference in voltages, the author designed and implemented electronic circuits on the one hand to reduce the generator's output voltage as well as filtering noise from the signal, then the micro-controller can measure the frequency. On the other hand, another circuit to amplify the voltage output from the micro controller and to the excitor of the generator's rotor. While the implemented controller validated the theoretical model, there is a need for further investigation of the non-linearity in the system since the generator produces limit cycle oscillations.